2004
DOI: 10.1097/01.asn.0000129337.50739.48
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Calcifications and Bone Histomorphometry in End-Stage Renal Disease

Abstract: Abstract. Arterial calcification (AC) is a common complication of end-stage renal disease (ESRD). The mechanisms responsible are complex, including disturbances of mineral metabolism and active expression of various mineral-regulating proteins. An inverse relationship between AC and bone density has been documented in uremic patients. In the study presented here, which included 58 patients with ESRD on hemodialysis (HD), bone-histomorphometry characteristics were compared with the AC scores (0 to 4) determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
394
8
27

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(443 citation statements)
references
References 41 publications
14
394
8
27
Order By: Relevance
“…The absence of correlations between histomorphometric indexes of bone turnover and coronary calcifications differ from reports by London et al (13,14), who found an association between systemic arterial calcifications (aorta and the main peripheral arteries) and indexes of low bone turnover, but not trabecular volume. One important difference between these publications resides in the arterial territories analyzed and the relationships of the different bone changes (bone volume, osteoblasts number, or tetracycline labeling), which do not necessarily reflect the same mechanisms.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…The absence of correlations between histomorphometric indexes of bone turnover and coronary calcifications differ from reports by London et al (13,14), who found an association between systemic arterial calcifications (aorta and the main peripheral arteries) and indexes of low bone turnover, but not trabecular volume. One important difference between these publications resides in the arterial territories analyzed and the relationships of the different bone changes (bone volume, osteoblasts number, or tetracycline labeling), which do not necessarily reflect the same mechanisms.…”
contrasting
confidence: 55%
“…In dialysis patients, coronary artery calcification score was found to be inversely correlated with vertebral bone mass (11,12). In addition, a high systemic arterial calcification score combined with bone histomorphometry suggestive of low bone activity was observed in hemodialysis patients (13,14). Arterial stiffening and low spine BMD or calcaneal osteopenia were significantly associated in CKD and hemodialysis patients (15)(16)(17).…”
mentioning
confidence: 86%
“…(5)(6)(7)(8) Importantly, deviation from the normal range of serum bone biomarkers predicts an increased risk of cardiovascular events, (9) and impaired bone remodeling is associated with increased vascular calcification. (10) In the general population, individuals with osteoporosis have increased atherosclerosis and coronary artery calcification (11)(12)(13)(14) and there is an inverse relationship between coronary artery calcification and bone mineral density (BMD) in both normal and CKD patients. (15) Agents that enhance bone quality also reduce cardiovascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…The evidences linking bone disease to vascular calcification in CKD patients have been based on bone turnover derangements and not on bone density. In studies with bone biopsy, an association between CAC and low bone turnover has been observed in CKD patients (17,34,35). It seems that the decreased bone formation rate leads to an inability of bone to buffer the calcium overload, predisposing to metastatic calcification (36).…”
Section: Discussionmentioning
confidence: 99%